Insights into the Antioxidant Mechanism of Newly Synthesized Benzoxazinic Nitrones: In Vitro and In Silico Studies with DPPH Model Radical - Stefania Marano; Cristina Minnelli; Lorenzo Ripani; Massimo Marcaccio; Emiliano Laudadio; Giovanna Mobbili; Adolfo Amici; Tatiana Armeni; Pierluigi Stipa (MDPI AG, 2021)
Synthetic nitrone spin-traps are being explored as therapeutic agents for the treatment of a wide range of oxidative stress-related pathologies, including but not limited to stroke, cancer, cardiovascular, and neurodegenerative diseases. In this context, increasing efforts are currently being made to the design and synthesis of new nitrone-based compounds with enhanced efficacy. The most researched nitrones are surely the ones related to α-phenyl-tert-butylnitrone (PBN) and 5,5-dimethyl-1-pyrroline N-oxide (DMPO) derivatives, which have shown to possess potent biological activity in many experimental animal models. However, more recently, nitrones with a benzoxazinic structure (3-aryl-2H-benzo[1,4]oxazin-N-oxides) have been demonstrated to have superior antioxidant activity compared to PBN. In this study, two new benzoxazinic nitrones bearing an electron-withdrawing methoxycarbonyl group on the benzo moiety (in para and meta positions respect to the nitronyl function) were synthesized. Their in vitro antioxidant activity was evaluated by two cellular-based assays (inhibition of AAPH-induced human erythrocyte hemolysis and cell death in human retinal pigmented epithelium (ARPE-19) cells) and a chemical approach by means of the α,α-diphenyl-β-picrylhydrazyl (DPPH) scavenging assay, using both electron paramagnetic resonance (EPR) spectroscopy and UV spectrophotometry. A computational approach was also used to investigate their potential primary mechanism of antioxidant action, as well as to rationalize the effect of functionalization on the nitrones reactivity toward DPPH, chosen as model radical in this study. Further insights were also gathered by exploring the nitrone electrochemical properties via cyclic voltammetry and by studying their kinetic behavior by means of EPR spectroscopy. Results showed that the introduction of an electron-withdrawing group in the phenyl moiety in the para position significantly increased the antioxidant capacity of benzoxazinic nitrones both in cell and cell-free systems. From the mechanistic point of view, the calculated results closely matched the experimental findings, strongly suggesting that the H-atom transfer (HAT) is likely to be the primary mechanism in the DPPH quenching.